2020
DOI: 10.1007/s43452-020-00103-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and modelling research on coach passengers’ safety in frontal impacts

Abstract: Road traffic accidents involving coaches do not happen very often, but they are very dangerous because they affect a large number of passengers. Coaches (or intercity buses) are not equipped with safety belt harnesses. Valid regulations do not impose any obligation on coach manufacturers to provide intercity buses with either two- or three-point safety belts. This fact may result from the unawareness of risks and injuries that might befall the passengers with no safety belts during accidents. That is the reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A scheme of the mechanical diagram of the MR damper is shown in Figure 3. The dampers can be used as comfort and noise protection elements, too [41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Figure 3 presents the general view of the soundproof partition of the bus motor.…”
Section: Methodsmentioning
confidence: 99%
“…A scheme of the mechanical diagram of the MR damper is shown in Figure 3. The dampers can be used as comfort and noise protection elements, too [41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Figure 3 presents the general view of the soundproof partition of the bus motor.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the impact of vibration may cause health problems and passenger injuries. 1 Research on the effect of impact force on the structural and mechanical system has been reported. Wei et al 2 noted that the combined effect of front compressive wave and back tensile wave are primary factors influencing the breakage of masonry walls under explosion impact load.…”
Section: Introductionmentioning
confidence: 99%
“…In the works [9] the authors observed that both in the case of the two-point safety system and the lack of belts, high acceleration values were recorded in the center of gravity of the head. Based on the research, it was found that only the three-point seat belt system ensures adequate passenger safety.…”
Section: Introductionmentioning
confidence: 99%